HUBUNGAN KETERAMPILAN MENGAJAR DAN MOTIVASI TERHADAP PRESTASI KERJA GURU IPS SMP NEGERI DI KABUPATEN HULU SUNGAI UTARA - Noor Adha Eriyadi (JURNAL SOCIUS, 2014)
This research aims (1) to indentify the level of teaching skill and working performance of Social Science (IPS) teachers at the Public Junior High Schools in the Regency of Hulu Sungai Utara, (2) to indentify the level of working motivation and working performance of IPS teachers at the Public Junior High Schools in the Regency of Hulu Sungai Utara, he method used in this research was descriptive quantitative method. The sample of this research was taken by using random sampling. The result of the research shows that (1) based on the respondents’ answers about teaching skill, approximately 64.45% of the respondents strongly agreed, while 31.10% of respondents agreed, 3.46% of respondents disagreed and 0.99% of respondents strongly disagreed. (2) based on the respondents’ answers about motivation, approximately 53.59% of respondents strongly agreed, while 41.62% of respondents agreed, 3.03% of respondents disagreed and 1.77% of respondents strongly disagreed. (3) based on the respondents’ answers about working performance, approximately 68.04% of respondents strongly agreed, while 26.83% of respondents agreed, 3.64% of respondents disagreed and 1.48% of respondents strongly disagreed. Teaching skill had a strong correlation with working performance of IPS teachers which can be identified from the value of ry1 = 0.832 in the interval of 0.80 – 1.000 with very strong criteria. Working motivation had a strong correlation with working performance of IPS teachers which can be seen from the value of ry2 = 0.768 in the interval of 0.60 – 0.779 with strong criteria. There was a positive and significant correlation between teaching skill and motivation together with the working performance of IPS teachers. The result of double correlation testing shows that the correlation value (R) was 0.850 with p = 0.000. Those three factors are related to each other in supporting working performance. Key Words: Teaching Skill, Working Motivation and Working Performance.